Pengaruh Akuntabilitas Keuangan Daerah Dan Sistem Pengendalian Internal Pemerintah Terhadap Tingkat Kemandirian Daerah Di Indonesia - Hasyim, Wahyudin; Pattawe, Abdul; Din, Muhammad; Furqan, Andi Chairil; Megawati, Megawati (Jurnal Akuntansi Manado (JAIM), 2024)
This research aims.to analyze the influence of regional financial accountability and.the effectiveness of.the Government.Internal Control.System (SPIP) in increasing regional independence. Using 542 regional government data consisting of Provinces/Districts/Cities during 2018-2021 with a sample of 2,168 observations. The results of this research show that regional financial accountability has a positive effect on regional independence, where increasing financial accountability contributes to increasing regional independence. Meanwhile, a strong SPIP also contributes significantly to regional independence, indicating that strengthening internal control can increase the efficiency and effectiveness of regional financial management. This research has implications for the importance of regional governments creating and implementing policies to realize accountability and improve financial zmanagement as a strategy to increase regional independence.